2004
DOI: 10.1097/00005537-200407000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Local Immunoglobulin E Production in the Pathophysiology of Noninvasive Fungal Sinusitis

Abstract: This is the first study to show that fungal-specific IgE may be demonstrated in sinus mucin. It was significantly associated with systemic fungal allergy and may play a role in a minority of fungal sinusitis patients in the absence of systemic fungal allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 21 publications
0
83
0
1
Order By: Relevance
“…18 Pant et al in his study demonstrated the significance of humoral immunity in the pathogenesis of AFRS. 19 He studied patients with eosinophilic mucin CRS, polypoid rhinosinusitis with or without fungal elements.…”
Section: Discussionmentioning
confidence: 96%
“…18 Pant et al in his study demonstrated the significance of humoral immunity in the pathogenesis of AFRS. 19 He studied patients with eosinophilic mucin CRS, polypoid rhinosinusitis with or without fungal elements.…”
Section: Discussionmentioning
confidence: 96%
“…The role of TH2 inflammation and type I hypersensitivity in the pathogenesis of AFS is supported by studies that document elevated fungal specific IgE in the serum of patients with suspected AFS [45,46]. In one study, fungal specific IgE was commonly found in the mucin of affected patients [47]. Staining for major basic protein and neutrophil elastase has revealed increased amounts of these proteins in the mucin of patients with AFS suggesting that neutrophil and eosinophil degrannulation contribute to pathogenesis of AFS [48].…”
Section: Allergic Fungal Sinusitismentioning
confidence: 98%
“…In 2004, Collins et al [39] identified fungus-specific IgE in paranasal sinus allergic mucin of patients with suspected AFRS undergoing endoscopic sinus surgery. These authors also evaluated systemic fungus-specific IgE levels in serum and detected fungus-specific IgE in sinus mucin in some patients in the absence of fungus-specific serum IgE [39].…”
Section: Localized Immunoglobulin E In Allergic Fungal Rhinosinusitismentioning
confidence: 99%